Identification of Student Errors In Solving Trigonometry Problems in Class X SMK Negeri 3 Palangka Raya - Dita, Alifya; Alihasan, Qodri; Haryani, Desti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2024)
This study aims to describe the errors and factors that cause students to make mistakes in solving trigonometry problems. This research is a descriptive research with a quantitative-qualitative approach. The data collection techniques in this study were tests and interviews. Based on the results of the study, the errors made by students were∶ (1) fact errors (68.55%), namely students did not write and incorrectly write the symbol or notation of the symbols